Atypical Causes of Urinary Tract Obstruction. (27th February 2019) - Yap, Ernie; Salifu, Moro; Ahmad, Tahir; Sanusi, A.; Joseph, Anthony; Mallappallil, Mary
Abstract : Acute kidney injury due to urinary tract obstruction invariably suggests lower urinary tract obstruction or bilateral ureteric obstruction since obstruction of a single kidney while the contralateral kidney is normal and not obstructed would not cause a perceptible rise in creatinine. Assuming a total body volume of 42 L, 70 kg male that generates approximately 1400 mg of creatinine daily (20 mg/kg/day) who has complete urinary tract obstruction would experience a 3.33 mg/dL per day increase in serum creatinine. Thus, for an individual who had prior normal renal function and who presents with a creatinine of 30 mg/dL, one could surmise that the obstructive pathology had lasted at least 10 days. However, the rise in serum creatinine is a poor marker of renal injury and subsequent prognosis. Urinary tract obstruction leading to AKI can be due to a variety of causes, and its management is tailored to the underlying etiology. This case series describes the varied clinical course of four patients at our center who experienced AKI from atypical causes of obstructive uropathy. Current and future diagnostic modalities and caveats in the treatment of this disease entity are also discussed.